2014
DOI: 10.36013/ijipem.v1i0.6
|View full text |Cite
|
Sign up to set email alerts
|

Google Technology in the Surveillance of Hand Foot Mouth Disease in Asia

Abstract: Background: Hand foot Mouth Disease (HFMD) is a worldwide Enteroviral infection; severe outbreaks have occurred recently in the US and Asia. Google technology has been shown to predict influenza epidemics and is a potential resource to track epidemics in developed countries where the use of Web-based searches is prevalent.Methods: Google Trends and Google Correlate were used to enumerate Web based search queries related to HFMD in three Asian regions and were compared to known seasonal variations and standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…This result is not only better than the error level generated when strictly using historical HFMD cases, the composite index, and the revised index but rather it is also 11.19% lower than the error level generated when combining the composite index with lagged CCDC data. While Cayce et al [8] found Google Trends to serve as a suitable tool for tracking HFMD trends in developed countries in Asia (e.g., Singapore and Japan), they also found that Google Trends is not strongly correlated with surveillance data in Hong Kong. This phenomenon may be more pronounced for developing countries where regional differences are significant.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This result is not only better than the error level generated when strictly using historical HFMD cases, the composite index, and the revised index but rather it is also 11.19% lower than the error level generated when combining the composite index with lagged CCDC data. While Cayce et al [8] found Google Trends to serve as a suitable tool for tracking HFMD trends in developed countries in Asia (e.g., Singapore and Japan), they also found that Google Trends is not strongly correlated with surveillance data in Hong Kong. This phenomenon may be more pronounced for developing countries where regional differences are significant.…”
Section: Discussionmentioning
confidence: 97%
“…The Baidu Index provides data on three spatial scales: country-, province-and city-wide. To date, the Baidu Index has been used to track influenza [6] and H7N9 [8] trends in China. However, previous studies have primarily focused on a single spatial scale [1,[11][12][13].…”
Section: Search Engine Datamentioning
confidence: 99%
See 1 more Smart Citation